2019
DOI: 10.1016/j.medmal.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary management of patients presenting with Lyme disease suspicion

Abstract: This is to our knowledge the first multidisciplinary center implemented in France for the management of patients presenting with LB suspicion related to polymorphous signs and symptoms. Several diagnoses could be confirmed or corrected, although some symptoms and complaints could not be explained. This cohort could improve our knowledge of LB and its differential diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 10 publications
5
23
1
2
Order By: Relevance
“…The strengths of our study are its population-based approach of disseminated LB, 4-year follow-up and comprehensive access to patient records from several different caregivers. Our patient cohort differed from other recent studies concerning confirmation of LB diagnosis [18,20,27,28]. The proportion of definite, probable and possible LB patients was higher (51%) in our patient cohort than the 13% to 23% reported in those studies.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The strengths of our study are its population-based approach of disseminated LB, 4-year follow-up and comprehensive access to patient records from several different caregivers. Our patient cohort differed from other recent studies concerning confirmation of LB diagnosis [18,20,27,28]. The proportion of definite, probable and possible LB patients was higher (51%) in our patient cohort than the 13% to 23% reported in those studies.…”
Section: Discussioncontrasting
confidence: 89%
“…The proportion of definite, probable and possible LB patients was higher (51%) in our patient cohort than the 13% to 23% reported in those studies. Furthermore, only 20% of our patients had been prescribed previous antimicrobial treatment effective for LB before referral compared to 50% to 85% in previous studies [18,20,27,28]. This might reflect our local guidelines to refer suspected disseminated LB for an infectious disease specialist consultation.…”
Section: Discussionmentioning
confidence: 71%
“…Some of these earlier studies were performed when first-generation Lyme disease serologic assays yielded higher false-positive rates than the current 2-tier standardized testing adopted in 1994–1995 [12]. Although one would anticipate improved diagnostic accuracy with improved specificity since the introduction of standardized 2-tier serology, the findings of this study suggest the opposite, with results that fall into a similar range of 9.6%–15.0%, as cited in recent French referral populations [23–25].…”
Section: Discussionmentioning
confidence: 50%
“…Overdiagnosis and overtreatment of Lyme borreliosis is frequent [1]. Recent studies have found that only 10 to 15% of patients consulting with a presumed diagnosis of Lyme borreliosis were actually found with Lyme borreliosis [2][3][4][5]. Psychiatric disorders, including somatic symptom and related disorders as well as depressive disorders, were found in 25% of 301 patients in Paris, France [2], and 42.5 % of 209 patients in Connecticut, USA [6].…”
Section: Introductionmentioning
confidence: 99%